Environmental life cycle assessment (LCA) of model massive timber and concrete buildings. Implementation of cross-laminated timber (CLT) in an educational facility at the Forest Botanical Garden Marszewo in Gdynia - Gierbienis, Marcin; Łukaszewski, Łukasz (Archives of Civil Engineering, 2026)
During the second decade of the 21st century, the effects of climate change became particularly noticeable, as population growth and aggressive urbanisation degraded the natural environment. In modern construction industry, the concepts of sustainable development and life cycle assessment (LCA) are important, covering the investment process from design and construction to operation and potential demolition. Wood, a natural raw material present in architecture for centuries, unites the ecological, economic and social principles of sustainable design. Thanks to innovative processing techniques such as cross-laminated timber (CLT) technology, wood can meet the challenges of modernity. Given the growing consumer interest in pro-environmental attitudes and the tightening of regulations within the European Union, the main emphasis will likely be on choosing environmentally friendly materials with a low carbon footprint, favourable energy balance, and ultimately, recovery or reuse potential. Based on this hypothesis, the paper presents a comparative LCA analysis of CLT and concrete technology for the implementation in an educational building at the Forest Botanical Garden Marszewo in Gdynia.